The Relationship of the Soviet Union with the Republic of Cyprus 1960-1964 - Michael, Despina (Études helléniques / Hellenic Studies, 2011)
This article will examine the early stages of the relationship between The Republic of Cyprus and the Soviet Union as it is revealed in a number of Ministry of Foreign Affairs Documents (Cyprus) 1960-1964 and other sources. Focus will be on the main concerns of the Soviet Union as they were expressed in official documents, regarding what was seen as Cyprus’ compromised sovereignty, its central role in the Cold War and NATO’s activities in the Eastern Mediterranean.